Legal Analysis on Interlink between International and National Instruments Towards Woman Rights in Indonesia - Prihatinah, Tri Lisiani (Indonesian Journal of International Law, 2021)
International instruments such as the Universal Declaration on Human Rights, the Internasional Covenants on Civil and Political Rights and Social and Cultural Rights, and the Convention for the Elimination of Discrimination Agaist Women (CEDAW) have led to what has been called a juridical revolution. Under these international instruments, the idea of all these rights including woman rights has been constitutionalized in almost all countries and practically all countries are now committed internationally to respect and ensure the woman rights of their citizens. In this paper international instruments relating the woman rights and their domestic enforceability are covered. Using juridical-normative approach, we discuss the domestic enforceability of international woman rights in Indonesia. The result showed that although women are guaranteed equality under Indonesian Constitution, considerable gaps exist between de jure and de facto equality for women. When there is a conflict within a monist approach, Indonesia tends to follow a doctrine of national law primate. In a case of instruments conflict between woman rights at national/local instruments and international one, then international instument is put aside.